PATH FOLLOWING PROBLEM FOR UAV CARRYING PENDULUM - Shahinyan, Arman S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2021)
The linearized dynamics of a UAV is considered along with a pendulum hanging from it. The state trajectories of the center of mass of the UAV are given. Given the trajectory of the center of mass of the UAV and the state trajectory of its yaw angle, we have to find the control actions and conditions under which the UAV would follow the path while holding the pendulum stable around its lower equilibrium point. The problem is solved using the method for solving inverse problems of dynamics. All the state trajectories of the system and all the control actions are calculated. The condition is obtained under which a solution to the path following problem exists. A specified simple trajectory is chosen as an example for visualizing the results.
Keywords: dynamic systems; control theory; optimal stabilization; quadcopter